2018
DOI: 10.1016/j.mib.2018.01.013
|View full text |Cite|
|
Sign up to set email alerts
|

The soil microbiome — from metagenomics to metaphenomics

Abstract: Soil microorganisms carry out important processes, including support of plant growth and cycling of carbon and other nutrients. However, the majority of soil microbes have not yet been isolated and their functions are largely unknown. Although metagenomic sequencing reveals microbial identities and functional gene information, it includes DNA from microbes with vastly varying physiological states. Therefore, metagenomics is only predictive of community functional potential. We posit that the next frontier lies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
254
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(278 citation statements)
references
References 45 publications
3
254
1
Order By: Relevance
“…Thus far, the limited studies of soil viruses have identified few AMGs relative to studies of marine environments. This may be due to under-sampling, or difficulties in identifying AMGs; since AMGs are homologs of host genes, they can be mistaken for microbial contamination (103) and thus are more difficult to discern in bulk-soil metagenomes (whereas marine virology has been dominated by viromes); also, microbial gene function is more poorly understood in soils (104). Alternately, soil viruses could indeed encode fewer AMGs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, the limited studies of soil viruses have identified few AMGs relative to studies of marine environments. This may be due to under-sampling, or difficulties in identifying AMGs; since AMGs are homologs of host genes, they can be mistaken for microbial contamination (103) and thus are more difficult to discern in bulk-soil metagenomes (whereas marine virology has been dominated by viromes); also, microbial gene function is more poorly understood in soils (104). Alternately, soil viruses could indeed encode fewer AMGs.…”
Section: Resultsmentioning
confidence: 99%
“…Our simulation results suggest that metabolic activation/deactivation strategies of microbial functional groups may be a key control of C turnover in soil. These modelbased implications could be tested with targeted experiments that enable spatially resolved measurements of microbial community composition and C fluxes at the microhabitat scale by extending existing approaches (e.g., Poll et al, 2006) and using novel techniques such as flow cells (Krueger et al, 2018) in combination with functional multilayered omics approaches (Jansson and Hofmockel, 2018;Sergaki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recent efforts are mapping the microbiome of Earth for different habitat types (see for instance the Earth Microbiome project 1 and the Global Ocean Microbiome project 2 ), however, the connection between environment and population microbiome is still lacking and difficult to predict. While it is true that consistent efforts have been devoted to the analysis of diseaseor symptom-specific alterations of the microbiome in relation to external environmental agents (Bucci et al, 2012;Davenport et al, 2017;Karkman et al, 2017;Mitmesser and Combs, 2017), a large gap exists in the analysis of how the spatiotemporal distribution of microbiota in the environment [e.g., soils (Jansson and Hofmockel, 2018), plants (Wackett, 2019), water (Lee et al, 2016), and natural hosts (Bahrndorff et al, 2016;Degli Esposti and Martinez Romero, 2017)] affects the microbiome in natural and human communities. Note that this ecological investigation, guided by theory, targeted monitoring and models (see section "Pattern-Oriented Models"), does not necessarily need to focus on health but on any spatio-temporal pattern manifesting ecological states of co-evolving microbiomes such as biodiversity patterns [see Parfrey and Knight (2012) and Ochman et al (Moeller et al, 2016b;Ochman, 2016)] and other socio-ecological ecosystem services.…”
Section: Human -Environment-microbiome Nexusmentioning
confidence: 99%